Histopathological Correlations between Mediastinal Fat-Associated Lymphoid Clusters and the Development of Lung Inflammation and Fibrosis following Bleomycin Administration in Mice - Elewa, Yaser Hosny Ali; Ichii, Osamu; Takada, Kensuke; Nakamura, Teppei; Masum, Md. Abdul; Kon, Yasuhiro (Frontiers in Immunology, 2018)
Bleomycin (BLM) has been reported to induce lung inflammation and fibrosis in human and mice and showed genetic susceptibility. Interestingly, the C57BL/6 (B6) mice had prominent mediastinal fat-associated lymphoid cluster (MFALCs) under healthy condition, and showed susceptibility to development of lung fibrosis following BLM administration. However, the pathogenesis of lung lesion progression, and their correlation with MFALC morphologies, remain to be clarified. To investigate the correlations between MFALC structures and lung injuries in B6 mice, histopathological examination of mediastinal fat tissues (MFT) and lungs was examined at 7 and 21 days (d) following a single 50 µL intranasal (i.n.) instillation of either BLM sulfate (5 mg/kg) (BLM group) or PBS (control group). The lung fibrosis was examined by Masson’s trichrome (MT) stain of paraffin sections and mRNA expression levels of Col1a1, Col3a1, and Acta2 in different frozen lung samples. Furthermore, immunohistochemistry for CD3, B220, Iba1, Gr1, BrdU, LYVE-1, and PNAd was performed to detect T- and B-cells, macrophages, granulocytes, proliferating cells, lymph vessels (LVs), and high endothelial venules (HEVs). We found that MFALCs were more abundant in the BLM group as compared to the control group. The lung of BLM group developed pneumonitis with severe cellular infiltrations at 7d and significant collagen deposition (MT) and higher expression of Col1a1, and Col3a1 at 21d post-administration. Numerous immune cells, proliferating cells, HEVs, and LVs were observed in both MFALCs and lungs of the BLM group. Interestingly, PNAd+ HEVs were observed in the lungs of the BLM group, but not the control group. Moreover, numerous Gr1+ polymorphonuclear and mononuclear-like ring cells were found in the MFALCs and lungs of the BLM group. Interestingly, flow cytometric analysis revealed a significant increase of B-cell populations within the MFALCs of BLM group suggesting a potential proliferative induction of B-cells following inflammation. Furthermore, significant positive correlations were observed between quantitative parameters of these immune cells in both the lungs and MFALCs. Thus, we suggest a potentially important role for MFALCs and HEVs in the progression of lung disease, especially in inflammatory lung disease.